A Bibliography of Chinese Language Materials on the People's Communes - Ma, Wei-yi (Michigan Monographs In Chinese Studies, 2020)
A research tool for scholars studying modern China, particularly those focusing on the post-1949 communal system and economy. The work includes full bibliographic references to some 2,800 essay, articles, pamphlets, and other materials in Chinese taken from more than 130 publications, primarily from mainland. The entries are arranged are arranged topically with annotations. Includes a geographic index to the communes referred to in the listed items.